The Moro National Liberation Front, 1972-1978 an annotated bibliography - Domingo, Luis B.; Vallejo, Rosa M.; Abubakar, Asiri J. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1978)
The Moro National Liberation Front (MNLF) is the main secessionists group fighting for autonomy in Mindanao. It is a sophisticated organization with a central committee, a political bureau, a propaganda and intelligence bureau, provincial/barrio committees, and a regular army.
This annotated bibliography is a compilation of primary and secondary sources, published and unpublished materials about the MNLF available in four libraries in Metro Manila, namely: the Ateneo de Manila Rizal Library , Asian Development Bank Library, Philippine Center for Advanced Studies Library and the University of the Philippines Main Library. It contains nine-hundred four single entries, arranged alphabetically by broad subject categories. Under each heading the arrangement is alphabetically by author or title. Each entry is provided with an item number from one to nine-hundred four. This is the number that is referred to in the subject, keyword and author indexes which have been provided to facilitate the location of specific items.
This work is divided into two parts. Part I, Chapter I - Introduction, includes a brief historical background of the Mindanao conflict. Chapter II - The MNLF: A Chronology of Events, provides some insights on the MNLF as the main Moro secessionist organization in the Southern Philippines. It also presents the most important events from the initial peace talks in Jeddah to the breakdown of peace negotiations in Manila, including the tragic Patikul massacre. Part II is the main bibliography divided into forty-five subject categories arranged alphabetically.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Moro National Liberation Front--Bibliography.; Muslims in the Philippines--Bibliography.